Enhancing the Therapeutic Efficacy of Bone Marrow-Derived Mononuclear Cells with Growth Factor-Expressing Mesenchymal Stem Cells for ALS in Mice - Tomoya Terashima; Shuhei Kobashi; Yasuhiro Watanabe; Mami Nakanishi; Naoto Honda; Miwako Katagi; Natsuko Ohashi; Hideto Kojima (iScience, 2020)
Summary: Several treatments have been attempted in amyotrophic lateral sclerosis (ALS) animal models and patients. Recently, transplantation of bone marrow-derived mononuclear cells (MNCs) was investigated as a regenerative therapy for ALS, but satisfactory treatments remain to be established. To develop an effective treatment, we focused on mesenchymal stem cells (MSCs) expressing hepatocyte growth factor, glial cell line-derived neurotrophic factor, and insulin-like growth factor using human artificial chromosome vector (HAC-MSCs). Here, we demonstrated the transplantation of MNCs with HAC-MSCs in ALS mice. As per our results, the progression of motor dysfunction was significantly delayed, and their survival was prolonged dramatically. Additional analysis revealed preservation of motor neurons, suppression of gliosis, engraftment of numerous MNCs, and elevated chemotaxis-related cytokines in the spinal cord of treated mice. Therefore, growth factor-expressing MSCs enhance the therapeutic effects of bone marrow-derived MNCs for ALS and have a high potential as a novel cell therapy for patients with ALS.